2013
DOI: 10.1142/s0218271813300012
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of Entropy Spectra of Black Holes

Abstract: From the quasinormal modes (QNM) of black holes, we obtain the quantizations of the entropy and horizon area of black holes via Bohr-Sommerfeld quantization, based on Bohr's correspondence principle. For this, we identify the appropriate action variable of the classical system corresponding to a black hole. By considering the BTZ black holes in topologically massive gravity as well as Einstein gravity, it is found that the spectra of not the horizon areas but the entropies of black holes are equally spaced. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…This entropy spectrum is also equally spaced and the same with the rotating BTZ black holes in the Einstein gravity and higher derivative gravities such as TMG and NMG [49,50,29].…”
Section: Entropy Spectrum From the Asymptotic Quasinormal Modesmentioning
confidence: 74%
See 1 more Smart Citation
“…This entropy spectrum is also equally spaced and the same with the rotating BTZ black holes in the Einstein gravity and higher derivative gravities such as TMG and NMG [49,50,29].…”
Section: Entropy Spectrum From the Asymptotic Quasinormal Modesmentioning
confidence: 74%
“…Therefore, it is found that the entropy spectra of the Schwarzschild-dS and new type-dS black holes are equally spaced. In particular, it was found in lots of literatures [29,48,49,50,51,52,53,54,55,56] that the entropies of black holes in diverse gravity theories are quantized with same spacing. Our results are also consistent with the universal property of equidistant entropy spectrum.…”
Section: Entropy Spectrum From the Asymptotic Quasinormal Modesmentioning
confidence: 99%
“…Further, Eq. ( 2) was generalized to the hairy BHs (massive, charged, and rotating ones) as follows (see [14] and references therein):…”
Section: Introductionmentioning
confidence: 99%